Retailer and supplier collaboration: An application of drama theory - Handayati, Yuanita; Simatupang, Tugar M.; Sridharan, Ramaswami (2010)
Collaboration is a process in which several parties share knowledge and competence in order to make decisions and take actions that lead to performance improvements. However, conflicts amongst participants of collaboration often occur due to the different interests and perceptions. This study aims at analyzing the collaboration process among supply chain members, taking a case study of collaboration between Coca-Cola and Carrefour. Drama Theory is as a method in modeling, analysis, and understanding the strategic conflict. The results show that collaboration between Coca-Cola and Carrefour took place in two functions: marketing and supply chain. The former could be illustrated in three phases, which are, initiation phase, competition phase and collaboration phase in which Coca-Cola and Carrefour agreed to run promotion programs together and raised the trading term in the agreeable amount. The latter could be depicted in two phases, which are, operations phase and collaboration phase in which Coca-Cola agrees to improve the level of service to Carrefour. In return, Carrefour agrees to share information with Coca-Cola.